New directions in the treatment of opioid withdrawal. Issue 10241 (20th June 2020) - Srivastava, A Benjamin; Mariani, John J; Levin, Frances R
Summary: The treatment of opioid withdrawal is an important area of clinical concern when treating patients with chronic, non-cancer pain, patients with active opioid use disorder, and patients receiving medication for opioid use disorder. Current standards of care for medically supervised withdrawal include treatment with μ-opioid receptor agonists, (eg, methadone), partial agonists (eg, buprenorphine), and α2-adrenergic receptor agonists (eg, clonidine and lofexidine). Newer agents likewise exploit these pharmacological mechanisms, including tramadol (μ-opioid receptor agonism) and tizanidine (α2 agonism). Areas for future research include managing withdrawal in the context of stabilising patients with opioid use disorder to extended-release naltrexone, transitioning patients with opioid use disorder from methadone to buprenorphine, and tapering opioids in patients with chronic, non-cancer pain.